Labor in the Digital Economy - A Challenge or New Opportunities - Syarova, Elka (Research Papers, 2020)
The main purpose of the paper is to present and systemize some aspects of restructuring of the labor within the digital economy concept. The object of the study are the main factors and theoretical concepts concerning the changes in the nature of work, and its subject - challenges and opportunities for the development of labor and the workforce in a digital economy. The report presents the new characteristics of the workforce and the introduction of the new information and communication technologies, revealing some of the challenges and as well as the new opportunities for labor and labor development.
Keywords: Factors; Labor market; Labor